Switched and impulsive systems: analysis, design and applications, Zhengguo Li, Yengchai Soh, Changyun Wen; Springer, Berlin. Heidelberg, 2005, ISBN: 3-540-23952-9. - Sun, Z. (2014)
10.1016/j.automatica.2006.04.013